Transversal : poems - Noel, Urayoán (Camino del sol., 2021)
"This collection of poems continues the exploration of non-equivalent and innovative self-translation found in Buzzing Hemisphere, but with a more elegant take on form and with more attention to Puerto Rico and the Caribbean as sites of transversal (i.e. intersecting, non-hierarchical) poetics and politics. Noel's signature playfulness, intellect, and topical politics (including poems written in response to Hurricane María) are featured throughout, as well as very personal reflections on love, desire, and loss. The book's exploration of a stateless poetics of "unstatement" offers a counterpoint to the poetics of hemispheric "buzz" in Noel's previous collection"--